Modified carbonized and activated steel slag as well as preparation method and application thereof

By performing activation treatment of steel slag and co-curing treatment of CO2 curing, modified carbonized activated steel slag was prepared, and combined with calcium-based raw materials, aluminum-based raw materials and admixtures, the problem of insufficient improvement in performance of steel slag in cement in the prior art was solved, and the early strength of cement and the reduction of energy consumption was achieved.

CN119612985APending Publication Date: 2025-03-14WUHAN UNIV OF TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411872271.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the prior art, the direct use of steel slag or carbide steel slag as mineral blends does not improve the performance of cement, and commonly used modification methods such as grinding and carbonization may consume a lot of energy and have limited improvement in cement performance.

Method used

By performing activation treatment on the steel slag and co-curing treatment of CO2 curing, the existence forms of Fe and Ca in the steel slag are optimized, and impurity ions are solidly dissolved in the mineral structure by calcination to prepare modified carbonized activated steel slag. The main ore phase of the modified carbonized activated steel slag is Ca2AlxFe2-xO5, and the secondary ore phase is C2S. It is combined with calcium-based raw materials, aluminum-based raw materials and admixtures to make a premature blend.

Benefits of technology

It effectively improves the early strength of cement, reduces the calcination temperature and energy consumption, reduces the adverse effects of impurity ions on the hydration of cement-based materials, and improves the utilization rate of steel slag.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses modified carbonized activated steel slag as well as a preparation method and application thereof. The preparation method comprises the following steps: activating steel slag by adopting an activating solution, adjusting the pH value to 7-8 after first stirring, and then carrying out second stirring, filtering, washing, drying, grinding, sieving and carbonizing to obtain carbonized and activated steel slag; and uniformly mixing the carbonized and activated steel slag, a calcium-based raw material and an aluminum-based raw material, calcining, quenching and grinding to obtain the modified carbonized and activated steel slag. The steel slag is subjected to chemical treatment and CO2 curing synergistic treatment, so that the existence forms of Fe and Ca in the steel slag can be optimized, and sintering is facilitated; impurity ions can be dissolved in a mineral structure through calcination, mineral lattice defects are improved, the calcination temperature is effectively reduced, and meanwhile the adverse effect of the impurity ions on hydration of the cement-based material is reduced. The early strength admixture prepared by compounding the modified carbonized activated steel slag, the silica fume, the metakaolin and the additive can effectively improve the early strength of the cement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a modified carbonized activated steel slag and a preparation method and application thereof. Background Art

[0002] Steel slag is an industrial waste produced during the steelmaking process. It has a large stockpile and can be used as a mineral admixture in the field of building materials. However, since steel slag contains a large amount of inert minerals, such as γ-C 2 S, FeO, etc., failed to have good performance after being added to cement. The existing technology improves the performance of silicate cement by modifying steel slag and using it as a mineral admixture. However, the commonly used modification methods currently only increase the hydration activity of steel slag by grinding, which may consume a lot of energy and have limited improvement in cement performance. In addition, the existing technology also carbonizes steel slag and then adds it to cement, but the carbonized steel slag may contain impurity ions, and its impact on cement performance needs to be verified.

[0003] Therefore, there is an urgent need to provide a modified steel slag to optimize the incorporation method of steel slag in cement, so as to further improve the performance of cement. Summary of the invention

[0004] The purpose of the present invention is to overcome the above-mentioned technical deficiencies, propose a modified carbonized activated steel slag and its preparation method and application, and solve the technical problem in the prior art that directly using steel slag or carbonized steel slag as a mineral admixture does not sufficiently improve the performance of cement.

[0005] In a first aspect, the present invention provides a method for preparing modified carbonized activated steel slag, comprising the following steps: The steel slag is activated by using an activation liquid, the pH value is adjusted to 7-8 after the first stirring, and then the steel slag is activated by the second stirring, filtering, washing, drying, grinding, screening and carbonizing to obtain carbonized activated steel slag; The carbonized activated steel slag, the calcium-based raw material and the aluminum-based raw material are uniformly mixed, calcined, rapidly cooled and ground to obtain the modified carbonized activated steel slag; wherein the main mineral phase of the modified carbonized activated steel slag is Ca 2 Al x Fe 2-x O 5 , and 0.66≤x≤1.33, the secondary mineral phase is C 2 S.

[0006] In a second aspect, the present invention provides a modified carbonized activated steel slag, which is obtained by the preparation method of the modified carbonized activated steel slag provided in the first aspect of the present invention.

[0007] In a third aspect, the present invention provides an early strength admixture based on modified carbonized activated steel slag, wherein the raw materials include, by weight: 85-93 parts of modified carbonized activated steel slag, 5-10 parts of metakaolin, 1-5 parts of silica fume, and 0.01-0.1 parts of an admixture; wherein the admixture is at least one of triethanolamine, ethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid, and hydroxyethylethylenediaminetriacetic acid.

[0008] In a fourth aspect, the present invention provides a method for preparing an early strength admixture based on modified carbonized activated steel slag, comprising the following steps: The modified carbonized activated steel slag, metakaolin, silica fume and admixture are uniformly mixed to obtain an early strength admixture based on the modified carbonized activated steel slag.

[0009] In a fifth aspect, the present invention provides the use of the above-mentioned early strength admixture based on modified carbonized activated steel slag in the preparation of cement products.

[0010] Compared with the prior art, the beneficial effects of the present invention include: The present invention chemically treats steel slag and CO 2 The solidification synergistic treatment can optimize the existence form of Fe and Ca in the steel slag, which is beneficial to the firing; the impurity ions can be dissolved in the mineral structure through calcination, the mineral lattice defects can be improved, the calcination temperature can be effectively reduced, the energy consumption and carbon dioxide emissions can be reduced, and the adverse effects of impurity ions on the hydration of cement-based materials can be reduced. The early strength admixture prepared by the present invention using the modified carbonized activated steel slag and silica fume, metakaolin and admixtures can effectively improve the early strength of cement. DETAILED DESCRIPTION

[0011] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0012] In a first aspect, the present invention provides a method for preparing modified carbonized activated steel slag, comprising the following steps: S1, activating the steel slag with an activation liquid, adjusting the pH to 7-8 after a first stirring, and then performing a second stirring, filtering, washing, drying, grinding, screening, and carbonizing to obtain carbonized activated steel slag; S2, the carbonized activated steel slag, the calcium-based raw material and the aluminum-based raw material are mixed evenly, and then calcined, rapidly cooled and ground to obtain modified carbonized activated steel slag; wherein the main ore phase of the modified carbonized activated steel slag is Ca 2 Al x Fe 2-x O 5 , and 0.66≤x≤1.33, the secondary mineral phase is C 2 S.

[0013] After the steel slag is activated, the binding state of impurity ions in the steel slag structure is destroyed, which promotes the subsequent carbonization degree; and carbonization can convert CaO in minerals such as calcium silicate, calcium hydroxide and some calcium ferrite in the activated steel slag into CaCO 3 At the same time, combined with the impurity ions generated after the activation treatment, the calcination temperature is effectively reduced to promote the formation of the target mineral. The present invention designs the mineral composition of the modified carbonized activated steel slag according to the chemical composition of the carbonized activated steel slag. The main mineral phase of the modified carbonized activated steel slag is Ca 2 Al x Fe 2-x O 5 , where 0.66≤x≤1.33, the secondary mineral phase is C 2 S, the required insufficient calcium and aluminum elements are supplemented with calcium-based raw materials and aluminum-based raw materials. Specifically, according to the silicon content in the carbonized activated steel slag, the calcium content required to convert it into the secondary mineral phase dicalcium silicate is determined; according to the iron content in the carbonized activated steel slag, the calcium content required to convert it into the main mineral phase Ca 2 Al x Fe 2-x O 5 The required calcium content and aluminum content are determined by adding the corresponding difference between the calcium-based raw materials and the aluminum-based raw materials. Since there are many impurity ions in the steel slag, the modified carbonized activated steel slag of the present invention can dissolve the impurity ions in the mineral structure by using the calcination technology, which can reduce the adverse effects of the impurity ions on the hydration of cement-based materials on the one hand, and improve the mineral lattice defects on the other hand, effectively reduce the calcination temperature, and reduce energy consumption and carbon dioxide emissions.

[0014] In this embodiment, the main mineral phase Ca 2 Al x Fe 2-x O 5 Including C 6 AF 2 , C 4 AF and C 6 A 2 At least one of F.

[0015] In some preferred embodiments of the present invention, the main mineral phase Ca 2 Al x Fe 2-x O 5 Including C 4 AF. This mineral phase can be formed with lower energy efficiency in the system of the present invention, and at the same time has better hydration activity and better early strength improvement effect.

[0016] In this embodiment, in step S1, the steel slag is converter steel slag. Converter steel slag has a relatively high iron content, which is conducive to obtaining the modified carbonized activated steel slag of the target mineral composition of the present invention.

[0017] In this embodiment, in step S1, the chemical composition of the steel slag includes, by weight percentage: CaO 40%-50%, SiO 2 10%-15%, Al 2 O 3 1%-4%, Fe 2 O 3 20%-30%, the balance is loss on ignition and unavoidable impurities (such as MgO, etc.).

[0018] In this embodiment, in step S1, the particle size of the steel slag is ≤75 μm.

[0019] In this embodiment, in step S1, the composition of the activation solution includes: an inorganic acid, a chelating agent and water. In the activation solution of the present invention, the inorganic acid can react quickly with the alkaline oxide in the steel slag, thereby increasing the chemical activity of the steel slag; the chelating agent can promote the dissolution of the alkaline components in the steel slag, and form a synergistic activation effect with the inorganic acid. At the same time, the steel slag itself has a certain hydration activity, and the chelating agent can form a pH buffer system, which helps to maintain the stability of the pH value during the reaction and ensure the activation reaction. The present invention uses an activation solution to activate the steel slag, which can effectively improve the carbonization activity of the steel slag on the one hand. This is because: 1. The H in the activation solution + First, it can destroy the inert mineral structure in the steel slag, such as the RO phase, thereby enhancing the activity of the steel slag; second, it can increase the specific surface area of ​​the steel slag, which can fully react during carbonization; on the other hand, the Mg-O bond can be destroyed by the activation liquid, and Mg can more easily enter the belite mineral lattice during the subsequent calcination process, thereby improving the activity of the cement clinker based on the carbonized activated steel slag. In addition, compared with the direct use of steel slag, the existence form of Fe in the steel slag changes after being treated with the activation liquid, which can significantly reduce the Gibbs formation energy of the iron-containing intermediate phase minerals, and contribute to the formation of intermediate phase minerals during the subsequent calcination process. In addition, adjusting the pH of the activation system to 7-8 is also conducive to the subsequent carbonization activation reaction.

[0020] The inorganic acid is at least one of sulfuric acid, hydrochloric acid and nitric acid.

[0021] Wherein, the complexing agent is citric acid.

[0022] Among them, in the activation solution, the concentration of the inorganic acid is 0.009-0.09 mol / L, and the concentration of the complexing agent is 0.0009-0.012 mol / L.

[0023] In some specific embodiments of the present invention, in step S1, the activation solution is prepared by a 0.01-0.1 mol / L inorganic acid solution and a 0.01-0.1 mol / L complexing agent solution in a mass ratio of (8-10):1.

[0024] In this embodiment, in step S1, the mass ratio of the activation solution to the steel slag is (50-150):1.

[0025] In this embodiment, in step S1, the temperature of the first stirring is room temperature, and the time of the first stirring is 10-60 minutes.

[0026] In this embodiment, in step S1, sodium hydroxide solution is used to adjust the pH to 7-8.

[0027] Wherein, the concentration of the sodium hydroxide solution is 0.05-0.2 mol / L, further 0.1 mol / L.

[0028] In this embodiment, in step S1, the temperature of the second stirring is room temperature, and the time of the second stirring is 30-60 minutes.

[0029] In this embodiment, in step S1, during the screening process, the mesh number of the sieve is ≥ 200 mesh, for example, it can be 200 mesh, 300 mesh, 400 mesh, 500 mesh, 1000 mesh, etc.

[0030] In this embodiment, in step S1, the carbonization process includes: The activated steel slag is dispersed in water, and then a gas containing carbon dioxide is introduced. After the reaction is completed, the slag is dried to obtain carbonized activated steel slag.

[0031] Among them, the mass ratio of water to activated steel slag is (10-40):1.

[0032] The present invention does not limit the type of carbon dioxide-containing gas, and those skilled in the art can select it according to actual conditions. For example, the carbon dioxide-containing gas can be CO 2 Carbon dioxide gas with a volume concentration of >90%, also known as CO 2 Low concentration carbon dioxide waste gas with a volume concentration of 10-90%.

[0033] Among them, the ventilation rate of carbon dioxide-containing gas is 0.3-0.6 ml / min.

[0034] The present invention does not limit the time of the carbonization reaction, and those skilled in the art can select it according to the actual situation, and wait until the carbonization reaction is completed. The present invention can use phenolphthalein solution, pH meter, conductivity meter and other means to monitor and judge the changes in color, pH value and conductivity to determine the completion of the reaction. For example, if pH ≤ 7, the reaction is completed.

[0035] In this embodiment, in step S2, during the calcination process, the heating rate is 10-20°C / min, the calcination temperature is 1250-1320°C, and the calcination time is 5550-9720s. The present invention can fully react to form the target mineral by controlling the calcination temperature within the above range. If the calcination temperature is too high, the sample will melt and damage the furnace; if the calcination temperature is too low, the reaction will be insufficient and the calcium silicate mineral cannot be stably generated.

[0036] In this embodiment, in step S2, the rapid cooling method is: cooling to below 100° C. within 5 minutes.

[0037] The present invention does not limit the types of calcium-based raw materials and aluminum-based raw materials, and those skilled in the art can make a selection according to actual conditions. For example, the calcium-based raw materials may be calcium carbonate, calcium oxide, shells, etc.; the aluminum-based raw materials may be aluminum oxide, bauxite, aluminum ash, etc.

[0038] In this embodiment, in step S2, the average particle size of the modified carbonized activated steel slag is ≤75 μm.

[0039] In a second aspect, the present invention provides a modified carbonized activated steel slag, which is obtained by the preparation method of the modified carbonized activated steel slag provided in the first aspect of the present invention.

[0040] In a third aspect, the present invention provides an early strength admixture based on modified carbonized activated steel slag, wherein the raw materials include, by weight: 85-93 parts of modified carbonized activated steel slag, 5-10 parts of metakaolin, 1-5 parts of silica fume, and 0.01-0.1 parts of admixture.

[0041] The present invention utilizes modified carbonized activated steel slag in coordination with silica fume, metakaolin and admixtures to effectively improve the early strength of cement. Specifically, modified carbonized activated steel slag and metakaolin can simultaneously generate hydration products such as hydrated calcium silicate and hydrated calcium ferrite when the cement-based material is hydrated, silica fume can compact the slurry structure and reduce the porosity, and the above components and cement-based materials can simultaneously enhance the early strength; the admixture can promote the reactivity of the early strength admixture.

[0042] In this embodiment, the average particle size of the metakaolin is 10-40 μm.

[0043] In this embodiment, the average particle size of the silica fume is 1-10 μm.

[0044] In this embodiment, the additive is at least one of triethanolamine, ethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid, and hydroxyethylethylenediaminetriacetic acid.

[0045] In a fourth aspect, the present invention provides a method for preparing an early strength admixture based on modified carbonized activated steel slag, comprising the following steps: The modified carbonized activated steel slag, metakaolin, silica fume and admixture are uniformly mixed to obtain an early strength admixture based on the modified carbonized activated steel slag.

[0046] In this embodiment, the mixing time is 6-10 hours.

[0047] In a fifth aspect, the present invention provides the use of the above-mentioned early strength admixture based on modified carbonized activated steel slag in the preparation of cement products.

[0048] After the early strength admixture based on modified carbonized activated steel slag is compounded with cement-based materials, the admixture can generate Fe 3+ , Ca 2+ Nucleation sites can provide more formation space for hydration products, effectively promote hydration activity, and thus improve the early strength of silicate cement.

[0049] In this embodiment, the dosage of the early strength admixture based on modified carbonized activated steel slag is 10%-40% of the mass of the cement-based material.

[0050] In the following embodiments and comparative examples of the present invention, the main chemical components of the common steel slag and carbonized activated steel slag used are shown in Table 1 below.

[0051] Table 1

[0052] The carbonized activated steel slag is prepared by the following steps: (1) Weigh ordinary steel slag with a particle size of ≤75 μm and place it in a beaker. Add activation solution (prepared with 0.1 M dilute sulfuric acid and 0.1 M citric acid solution in a mass ratio of 8:1) and the mass ratio of activation solution to steel slag is 150:1. Stir for 10 min. (2) After stirring, add 0.1 M NaOH until the pH is 7, and then stir for 30 minutes; (3) After stirring, filtering, washing, drying, grinding, and then passing through a 200-mesh sieve to obtain activated steel slag; (4) Place the activated steel slag in a beaker, add deionized water at a water-cement ratio of 40:1, and introduce CO at a rate of 0.3 ml / min. 2 (volume concentration ≥ 99%), and stop when pH = 7. The carbonized steel slag is dried to obtain carbonized activated steel slag.

[0053] Example 1 This embodiment provides a method for preparing modified carbonized activated steel slag, comprising the following steps: (1) Design and modify the mineral composition of carbonized activated steel slag according to its chemical composition. Its main mineral phase is C 4 AF, secondary mineral phase is C 2 S; 100 parts by weight of carbonized activated slag with 18 parts by weight of CaCO 3 With 13 parts by weight of Al 2 O 3 ; (2) Carbonized activated steel slag, CaCO 3 With Al 2 O 3 After being evenly mixed, the mixture is calcined at 1320°C, a heating rate of 20°C / min, and a calcination time of 5760s, and then rapidly cooled to room temperature. The calcined product is ground to an average particle size of ≤75μm to obtain modified carbonized activated steel slag.

[0054] This embodiment also provides a method for preparing an early strength admixture based on modified carbonized activated steel slag, comprising the following steps: (1) Weigh the following components in parts by weight: 85 parts of modified carbonized activated steel slag, 10 parts of metakaolin with an average particle size of 40 μm, 5 parts of silica fume with an average particle size of 10 μm, and 0.01 parts of triethanolamine.

[0055] (2) The weighed raw materials were mixed in a mixer for 10 h to obtain an early strength admixture based on modified carbonized activated steel slag.

[0056] This embodiment also provides the use of the above-mentioned early strength admixture based on modified carbonized activated steel slag in the preparation of cement products, comprising the following steps: The early strength admixture based on modified carbonized activated steel slag prepared in this embodiment was added to P·I type silicate cement (the adding ratio was 40% of the mass of silicate cement, and the water-binder ratio (i.e., the mass ratio of water to the early strength admixture and the total amount of cement) was 0.5) to prepare a standard sample of 40 mm×40 mm×160 mm. The compressive strength of the sample was tested according to GB / T 17671 standard. The results showed that the 3d compressive strength of the sample was 27.7 MPa, and the 7d compressive strength was 37.6 MPa.

[0057] Example 2 This embodiment provides a method for preparing an early strength admixture based on modified carbonized activated steel slag, comprising the following steps: (1) Weigh the following components in parts by weight: 93 parts of the modified carbonized activated steel slag prepared in Example 1, 5 parts of metakaolin with an average particle size of 10 μm, 2 parts of silica fume with an average particle size of 1 μm, and 0.1 parts of triethanolamine.

[0058] (2) The weighed raw materials were mixed in a mixer for 6 h to obtain an early strength admixture based on modified carbonized activated steel slag.

[0059] This embodiment also provides the use of the above-mentioned early strength admixture based on modified carbonized activated steel slag in the preparation of cement products, comprising the following steps: The carbonized activated steel slag early strength admixture prepared in this embodiment was added to P·I type silicate cement (the adding ratio was 40% of the mass of silicate cement, and the water-binder ratio was 0.5) to make a standard sample of 40mm×40mm×160mm. The compressive strength of the sample was tested according to GB / T17671 standard. The results showed that the 3d compressive strength of the sample was 28.3MPa, and the 7d compressive strength was 39.2MPa.

[0060] Example 3 This embodiment provides a method for preparing modified carbonized activated steel slag, comprising the following steps: (1) Design and modify the mineral composition of carbonized activated steel slag according to its chemical composition. Its main mineral phase is C 6 AF 2 , the secondary mineral phase is C 2 S; 100 parts by weight of carbonized activated slag with 4 parts by weight of CaCO 3 With 6 parts by weight of Al 2 O 3 ; (2) Carbonized activated steel slag, CaCO 3 With Al 2 O 3 After being evenly mixed, the mixture is calcined at 1250°C, a heating rate of 20°C / min, and a calcination time of 5550s, and then rapidly cooled to room temperature. The calcined product is ground to an average particle size of ≤75μm to obtain modified carbonized activated steel slag.

[0061] This embodiment also provides a method for preparing an early strength admixture based on modified carbonized activated steel slag, comprising the following steps: (1) Weigh the following components in parts by weight: 93 parts of modified carbonized activated steel slag, 6 parts of metakaolin with an average particle size of 40 μm, 1 part of silica fume with an average particle size of 10 μm, and 0.1 part of triethanolamine.

[0062] (2) The weighed raw materials were mixed in a mixer for 6 h to obtain an early strength admixture based on modified carbonized activated steel slag.

[0063] This embodiment also provides the use of the above-mentioned early strength admixture based on modified carbonized activated steel slag in the preparation of cement products, comprising the following steps: The carbonized activated steel slag early strength admixture prepared in this embodiment was added to P·I type silicate cement (the adding ratio was 40% of the mass of silicate cement, and the water-binder ratio was 0.5) to make a standard sample of 40mm×40mm×160mm. The compressive strength of the sample was tested according to GB / T17671 standard. The results showed that the 3d compressive strength was 26.2MPa and the 7d compressive strength was 34.8MPa.

[0064] Example 4 This embodiment provides a method for preparing modified carbonized activated steel slag, comprising the following steps: (1) Design and modify the mineral composition of carbonized activated steel slag according to its chemical composition. Its main mineral phase is C 6 A 2 F, secondary mineral phase is C 2 S; 100 parts by weight of carbonized activated slag with 47 parts by weight of CaCO 3 With 27 parts by weight of Al 2 O 3 ; (2) Carbonized activated steel slag, CaCO 3 With Al 2 O 3 After being evenly mixed, the mixture is calcined at 1320°C, a heating rate of 10°C / min, and a calcination time of 9720s, and then rapidly cooled to room temperature. The calcined product is ground to an average particle size of ≤75μm to obtain modified carbonized activated steel slag.

[0065] The preparation method of the early strength admixture based on modified carbonized activated steel slag provided in this embodiment is the same as that in Example 1.

[0066] This embodiment also provides the use of the above-mentioned early strength admixture based on modified carbonized activated steel slag in the preparation of cement products, comprising the following steps: The early strength admixture based on modified carbonized activated steel slag prepared in this embodiment was added to P·I type silicate cement (the adding ratio was 40% of the mass of silicate cement, and the water-binder ratio was 0.5) to make a standard sample of 40 mm×40 mm×160 mm. The compressive strength of the sample was tested according to GB / T 17671 standard. The results showed that the 3d compressive strength was 27.2 MPa and the 7d compressive strength was 36.1 MPa.

[0067] Example 5 This embodiment provides an application of an early strength admixture based on modified carbonized activated steel slag in the preparation of cement products, comprising the following steps: The early strength admixture based on modified carbonized activated steel slag prepared in Example 1 was added to P·I type silicate cement (the adding ratio was 10% of the mass of silicate cement, and the water-binder ratio was 0.5) to make a standard sample of 40mm×40mm×160mm. The compressive strength of the sample was tested according to GB / T 17671 standard. The results showed that the 3d compressive strength was 30.7MPa and the 7d compressive strength was 41.9MPa.

[0068] Comparative Example 1 Compared with Example 1, the only difference is that this comparative example only uses P·I type silicate cement to make cement samples, which are as follows: P·I type silicate cement was made into a standard specimen of 40mm×40mm×160mm with a water-cement ratio of 0.5. The compressive strength of the specimen was tested in accordance with GB / T 17671 standard. The results showed that the 3d compressive strength of the specimen was 22.9MPa and the 7d compressive strength was 30.8MPa.

[0069] Comparative Example 2 Compared with Example 1, the only difference is that in the preparation method of the admixture in this comparative example, the modified carbonized activated steel slag is replaced by ordinary steel slag.

[0070] The admixture prepared in this comparative example was added to P·I type silicate cement (the adding ratio was 40% of the mass of silicate cement, and the water-binder ratio was 0.5) to make a standard specimen of 40mm×40mm×160mm. The compressive strength of the specimen was tested in accordance with GB / T 17671 standard. The results showed that the 3d compressive strength of the specimen was 13.3MPa, and the 7d compressive strength was 19.6MPa.

[0071] Comparative Example 3 Compared with Example 1, the only difference is that in the preparation method of the admixture in this comparative example, the modified carbonized activated steel slag is replaced by carbonized activated steel slag.

[0072] The admixture prepared in this comparative example was added to P·I type silicate cement (the adding ratio was 40% of the mass of silicate cement, and the water-binder ratio was 0.5) to make a standard specimen of 40mm×40mm×160mm. The compressive strength of the specimen was tested in accordance with GB / T 17671 standard. The results showed that the 3d compressive strength of the specimen was 20.7MPa, and the 7d compressive strength was 29.1MPa.

[0073] Comparative Example 4 Compared with Example 1, the only difference is that in the preparation method of modified steel slag in this comparative example, the mineral composition of modified steel slag is designed according to the chemical composition of ordinary steel slag, and its main mineral phase is C 4 AF, secondary mineral phase is C 2S; 100 parts by weight of ordinary steel slag with 31 parts by weight of CaCO 3 With 15 parts by weight of Al 2 O 3 .

[0074] The admixture prepared in this comparative example was added to P·I type silicate cement (the adding ratio was 40% of the mass of silicate cement, and the water-binder ratio was 0.5) to make a standard specimen of 40mm×40mm×160mm. The compressive strength of the specimen was tested in accordance with GB / T 17671 standard. The results showed that the 3d compressive strength of the specimen was 23.1MPa, and the 7d compressive strength was 31.0MPa.

[0075] Table 2 Compressive strength of various embodiments and comparative examples

[0076] It can be seen from Table 2 that, compared with Examples 1-5, no early-strength admixture was added in Comparative Example 1, and the 3-day compressive strength and 7-day compressive strength of the obtained cement product were both lower, indicating that the early-strength admixture based on modified carbonized activated steel slag prepared in the embodiment of the present invention effectively improved the early strength of the cement product and had an improving effect on the early hydration performance of silicate cement.

[0077] Compared with Example 1, in the preparation method of the admixture in Comparative Example 2, the modified carbonized activated steel slag is replaced with ordinary steel slag. The 3-day compressive strength and 7-day compressive strength of the obtained cement product are lower and significantly lower than those of Comparative Example 1 without adding the admixture, indicating that directly using ordinary steel slag to prepare the admixture will reduce the early strength of the cement product.

[0078] Compared with Example 1, in the preparation method of the admixture in Comparative Example 3, the modified carbonized activated steel slag is replaced by carbonized activated steel slag. The 3-day compressive strength and 7-day compressive strength of the obtained cement product are lower than those of Comparative Example 1, indicating that the use of carbonized activated steel slag to prepare admixtures is not conducive to improving the early strength of cement products.

[0079] Compared with Example 1, in the preparation method of modified steel slag in Comparative Example 4, the mineral composition of modified steel slag is designed according to the chemical composition of ordinary steel slag. The 3-day compressive strength and 7-day compressive strength of the obtained cement product are slightly increased compared with Comparative Example 1 without adding admixtures, but are still significantly lower than Example 1, indicating that the admixture directly made from modified steel slag prepared by mixing and calcining ordinary steel slag with silicon-based materials and aluminum-based materials as raw materials does not greatly improve the early strength of cement products.

[0080] Compared with the prior art, the beneficial effects of the present invention include: (1) The main mineral phase Ca in the modified carbonized activated steel slag of the present invention 2 Alx Fe 2-x O 5 It has excellent early hydration activity. At the same time, the impurity ions in the steel slag, such as P, Mg, etc., can be dissolved in the belite minerals and iron phase minerals, increasing the lattice defects and promoting the synergistic effect in cement-based materials.

[0081] (2) The present invention adopts modified carbonized activated steel slag mixed with kaolin, silica fume and admixtures. On the one hand, the reaction characteristics of modified carbonized activated steel slag with kaolin and silica fume can be used to synergistically couple and enhance the cement-based materials. On the other hand, the use of admixtures can make the various components evenly dispersed in the cement-based materials to avoid product agglomeration. At the same time, the strong correlation effect between the carbonized activated steel slag early strength admixture and the iron and aluminum in the cement-based materials is enhanced, which is beneficial to the enhancement of the early strength of the cement-based materials.

[0082] (3) After the carbonized activated steel slag early strength admixture is compounded with cement-based materials, the admixture can produce, for example, Fe 3+ , Ca 2+ Nucleation sites can provide more formation space for hydration products and effectively promote hydration activity.

[0083] (4) The early strength admixture based on modified carbonized activated steel slag of the present invention can improve the utilization rate of steel slag, reduce the influence of ordinary steel slag on silicate cement, and effectively promote the early strength of silicate cement.

[0084] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing modified carbonized activated steel slag, characterized in that: The following steps are involved: The steel slag is activated by using an activation liquid, the pH value is adjusted to 7-8 after the first stirring, and then the steel slag is activated by the second stirring, filtering, washing, drying, grinding, screening and carbonizing to obtain carbonized activated steel slag; The carbonized activated steel slag, the calcium-based raw material and the aluminum-based raw material are uniformly mixed, and then calcined, rapidly cooled and ground to obtain modified carbonized activated steel slag; Wherein, the main mineral phase of the modified carbonized activated steel slag is Ca2Al x Fe 2-x O5, and 0.66≤x≤1.33, the secondary mineral phase is C2S.

2. The method for preparing modified carbonized activated steel slag according to claim 1, characterized in that: The chemical composition of the steel slag includes: CaO 40%-50%, SiO2 10%-15%, Al2O3 1%-4%, Fe2O3 20%-30%, and the balance is ignition loss and unavoidable impurities; and / or, The particle size of the steel slag is ≤75 μm.

3. The method for preparing modified carbonized activated steel slag according to claim 1, characterized in that: The activation solution comprises: an inorganic acid, a complexing agent and water; wherein: The inorganic acid is at least one of sulfuric acid, hydrochloric acid and nitric acid; and / or, The complexing agent is citric acid; and / or, In the activation solution, the concentration of the inorganic acid is 0.009-0.09 mol / L, and the concentration of the complexing agent is 0.0009-0.012 mol / L.

4. The method for preparing modified carbonized activated steel slag according to claim 1, characterized in that: The mass ratio of the activation solution to the steel slag is (50-150):1; and / or, The temperature of the first stirring is room temperature, and the time of the first stirring is 10-60 minutes; and / or, The pH value is adjusted to 7-8 by using a sodium hydroxide solution, and the concentration of the sodium hydroxide solution is 0.05-0.2 mol / L; and / or, The temperature of the second stirring is room temperature, and the time of the second stirring is 30-60 minutes; and / or, During the sieving process, the mesh number of the sieve is ≥200 meshes.

5. The method for preparing modified carbonized activated steel slag according to claim 1, characterized in that: The carbonization process includes: The activated steel slag is dispersed in water, and then a carbon dioxide-containing gas is introduced. After the reaction is completed, the slag is dried to obtain carbonized activated steel slag; wherein, The mass ratio of water to the activated steel slag is (10-40): 1; and / or, The volume concentration of CO2 in the carbon dioxide-containing gas is ≥10%; and / or, The ventilation rate of the carbon dioxide-containing gas is 0.3-0.6 ml / min.

6. The method for preparing modified carbonized activated steel slag according to claim 1, characterized in that: During the calcination process, the heating rate is 10-20°C / min, the calcination temperature is 1250-1320°C, and the calcination time is 5550-9720s; and / or, The rapid cooling method is: cooling to below 100° C. within 5 minutes; and / or, The average particle size of the modified carbonized activated steel slag is ≤75 μm.

7. A modified carbonized activated steel slag, characterized in that: The modified carbonized activated steel slag is obtained by the preparation method of the modified carbonized activated steel slag according to any one of claims 1-6.

8. An early strength admixture based on modified carbonized activated steel slag, characterized in that: The raw materials include, by weight: 85-93 parts of modified carbonized activated steel slag, 5-10 parts of metakaolin, 1-5 parts of silica fume, and 0.01-0.1 parts of additives; wherein, The modified carbonized activated steel slag is the modified carbonized activated steel slag according to claim 7; The additive is at least one of triethanolamine, ethylenediaminetetraacetic acid, diethylenetriaminepentaacetic acid, and hydroxyethylethylenediaminetriacetic acid.

9. A method for preparing an early strength admixture based on modified carbonized activated steel slag as claimed in claim 8, characterized in that: The following steps are involved: The modified carbonized activated steel slag, metakaolin, silica fume and admixture are uniformly mixed to obtain an early strength admixture based on the modified carbonized activated steel slag.

10. Use of the early strength admixture based on modified carbonized activated steel slag as claimed in claim 9 in the preparation of cement products.